PENGUATAN KARAKTER RELIGIUS MELALUI PEMBIASAAN TILAWAH ASMAUL HUSNA DAN SHALAWAT SEBAGAI PENCEGAHAN PATOLOGI SOSIAL REMAJA PADA SISWA SMP - Ai Tien Munthaha S (QATHRUNÂ, 2022)
The big conclusion of this paper is that the character of the eighth-grade students of Dirghantara Middle School is Religious Character in the form of faith in piety and ukhkuwah instilling and applying students' religious values ​​in everyday life, both divine and human religiosity, getting used to praying 5 times a day, instilling good morals. being kind, inviting, and setting a good example, instilling an attitude of shame and fear of doing evil, and not wanting to commit acts of deviant social behavior, all of these are appropriate actions taken by the school. The purpose of this study was to describe the religious character of adolescents in junior high school students, students' perceptions of the forms and causes of social pathology, and efforts to strengthen religious character through habituation of recitations of Asmaul Huna and shalawat as prevention of adolescent social pathology in junior high school students at Dirghantara Legok Junior High School, Tangerang Regency. The research approach is descriptive qualitative and religious sociology, namely observing adolescent religious problems, especially junior high school students in strengthening religious character as prevention of adolescent social pathology in junior high school students and field research, namely research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. Data collection techniques were obtained by observation, interviews, and documentation. The respondents who were used as samples were 24 people. The results of the study show: (1) The religious characteristics of the eighth-grade students of Dirghantara Junior High School are: Behavior that reflects the character of faith and piety (imtaq) and ukhuwah Islamiah; (2) Students' perceptions of forms of adolescent social pathology in Dirghantara Junior High School students tend to be normal or normal delinquency, but besides that, some students have juvenile deviant behavior in students who require special handling of violent behavior (bullying) and fights between students (brawls). ); (3) Students' perceptions of the factors that cause social pathology are driven by internal factors (endogenous factors) this is because of the behavior that is already inherent in the perpetrator himself, the influence of physical conditions and personality that exist in him and external factors (exogenous factors), namely students can do pathology/social among teenagers in junior high school students can occur from outside themselves, such as from family environmental factors, schools, communities, playgroups, and mass media; (4) Strengthening religious character as prevention of adolescent social pathology in junior high school students is carried out through habituation of recitations of Asmaul Husna and shalawat, apart from the habit of instilling and applying students' religious values ​​in daily life, both religious which are divine and insanity.